Adaptive analysis framework for controlled environments plant production, case study in tropical lowland Malaysia - Shamshiri, Ramin; Wan Ismail, Wan Ishak; Ahmad, Desa (American Society of Agricultural and Biological Engineers (ASABE), 2014)
An adaptive analysis framework (AAF) for controlled environment production (CEP) of tomato was developed. The overall objective was to provide energy efficient strategies for achieving optimal air temperature, relative humidity (RH) and vapor pressure deficit (VPD) in tropical lowland (TL) conditions. The framework database (DB) was built according to peer-reviewed published works on tomato growth response (GR) functions. A case study was carried out in TL Malaysia by collecting sample temperature, RH and light condition (sun, night, cloud) data for 126 days from July to Dec 2013. The framework was used to determine environment responses (ER) at three GR references (GR=0, GR=0.55 and GR=1) for five growth stages (GS). Results showed significant difference between means of ER values in different GS and GR levels, indicating possible savings of energy up to 62% at GS=1, 17% at GS=2 and 30% at GS=3 to 5 in providing ideal climate condition for CEP of tomato.